THE STUDY OF THE OPTICAL PROPERTIES OF CYCLODEXTRIN-PHOTOSENSITIZER mTHPC COMPLEXES - M. V. Goltsev; N. A. Nedzvedz; V. P. Zorin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The photostability of complexes of the mTHPC photosensitizer with different types of cyclodextrins was studied. The photostability is a characteristic of the bond strength of the photosensitizer-carrier complex. The conclusions about the most appropriate type of cyclodextrin for photodynamic therapy were made. The optimal ratio of photosensitizer and carrier concentrations was determined.